Noble Metal Decoration and Presulfation on TiO2: Increased Photocatalytic Activity and Efficient Esterification of n-Butanol with Citric Acid - Yu Niu; Pan Huang; Fuying Li; Kai Yang; Jinbei Yang; Renzhang Wang; Cheng Lin; Ting Qiu (International Journal of Photoenergy)
TiO2 has been widely used as a key catalyst in photocatalytic reactions; it also shows good catalytic activity for esterification reactions. Different sulfated M-TiO2 nanoparticles (M = Ag, Au, Rh, and Pt) were prepared by photodeposition and ultrasonic methods. The results show that the noble metal nanoparticles, which were loaded onto a TiO2 surface, slightly affected the crystal phase and particle size of TiO2. Among all the catalysts, SO42-/Au-TiO2 exhibited the best catalytic activity in the esterification reaction for the synthesis of citric acid n-butyl acetate and in the decomposition of methyl orange, as confirmed by a high conversion rate of up to 98.2% and 100% degradation rate, respectively. This can be attributed to an increase in the Lewis acidity of the catalyst and increased separation efficiency of electron-hole pairs. This superior catalyst has great potential applications in esterification reactions and wastewater treatments.